Community structure of microzooplankton in a tropical estuary (Uppanar) and a mangrove (Pichavaram) from the southeast coast of India - Rajkumar, Mayalagu; Prabu, V. Ashok; Rahman, Mustafizur; Jenkinson, Ian R. (Marine Biological Association of India, 2022)
In the marine and estuarine waters of Cuddalore, the southeast coast of India microzooplankton have previously been sparingly investigated. Micro-zooplankton community structure (species composition, abundance, diversity, richness, evenness) of an estuary and mangroves of the Cuddalore and Pichavaram areas, southeast India were investigated in detail. Monthly samples were taken from April 2000 to March 2002, from four fixed stations. Micro-zooplankton taxon composition and abundance showed seasonal variations being highest in summer (45 to 50 ind./l in April to August 2000; 60 to 67.5 ind./l in April to June 2001) and lowest during the monsoon (6 to 16 ind./l in September to December 2000; 7 to 19 ind./l in October to December 2001). The total abundance of microzooplankton was in the range of 10.3-65.0 ind./l in Cuddalore areas (Stations 1 and 2) and 5.2 - 67.5 ind./l in Pichavaram mangroves (Stations 3 and 4). Over the study period, tintinnids dominated the microzooplankton community in terms of both abundance and species diversity. The remaining taxa included Radiolaria, Foraminifera, Rotifera, ciliates other than tintinnids, and metazoans. A total of 62 and 74 species of microzooplankton were recorded from Cuddalore and Pichavaram mangroves respectively. Canonical Correspondence Analysis (CCA) was applied to discriminate environmental factors associated with the microzooplankton community at the species level. The results of the study provide a basis for rational sustainable exploitation of Cuddalore waters and future research on its living resources. Furthermore, a comparison of results with studies from around the world showed a very strong, significant relationship between abundance and sampling methods underlining the need for standardized protocols.